2012
DOI: 10.1128/aem.01148-12
|View full text |Cite
|
Sign up to set email alerts
|

Production of Aromatic Compounds by Metabolically Engineered Escherichia coli with an Expanded Shikimate Pathway

Abstract: ABSTRACTEscherichia coliwas metabolically engineered by expanding the shikimate pathway to generate strains capable of producing six kinds of aromatic compounds, phenyllactic acid, 4-hydroxyphenyllactic acid, phenylacetic acid, 4-hydroxyphenylacetic acid, 2-phenylethanol, and 2-(4-hydroxyphenyl)ethanol, which are used in several fields of industries including pharmaceutical, agrochemical, antibiotic, flavor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 45 publications
4
156
0
Order By: Relevance
“…Although the activity of Ahr has recently been hinted at (18), we unequivocally demonstrate that this enzyme catalyzes the reduction of aliphatic aldehydes to alcohols with a substrate profile ranging, at least, from C 4 to C 16 and a selective preference for NADPH. Based on the experimental verification of its catalytic activity in this study, as well as others (18,23), a replacement of the current gene name, yjgB, with ahr (aldehyde reductase) is proposed to denote the catalytic function of this gene product.…”
Section: Discussionmentioning
confidence: 87%
“…Although the activity of Ahr has recently been hinted at (18), we unequivocally demonstrate that this enzyme catalyzes the reduction of aliphatic aldehydes to alcohols with a substrate profile ranging, at least, from C 4 to C 16 and a selective preference for NADPH. Based on the experimental verification of its catalytic activity in this study, as well as others (18,23), a replacement of the current gene name, yjgB, with ahr (aldehyde reductase) is proposed to denote the catalytic function of this gene product.…”
Section: Discussionmentioning
confidence: 87%
“…We also demonstrated that several aromatic homoamino acid analogs, including L-homotyrosine, could be produced using this system, even though the range of substrate specificity is moderately limited. We propose that various fine chemical materials, such as keto acids, hydroxy acids, and alco-hols, derived from aromatic homoamino acids can be produced by combining the L-Hph-producing strain with various enzymes that have been developed for industrial production of useful chiral building blocks (37). Additionally, detailed structure-based comparison between enzymes for producing L-Hph and other homoamino acids will allow us to generate novel homoamino acidproducing systems through protein engineering in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty aldehyde content however was small compared with total pool size for alkanes and FAs. Fatty aldehydes may be converted to fatty alcohols in E. coli cells by endogenous aldehyde reductases (32,33). We therefore also examined the fatty alcohol content of these cells.…”
Section: Conversion Of Fa To Alkanes Is Limited By the In Vivo Use Ofmentioning
confidence: 99%